Expression of vasa, piwi, and nanos during gametogenesis in Typosyllis antoni (Annelida, Syllidae). Issue 5 (9th August 2018) - Ponz‐Segrelles, Guillermo; Bleidorn, Christoph; Aguado, M. Teresa
Abstract : Although model species have proven to be crucial for developmental biology, the evo‐devo approach requires a broader picture across phylogeny. Herein, we try to expand the range of studied annelids by presenting a transcriptome of Typosyllis antoni as a tool for the study of developmental and evolutionary processes in Syllidae. Moreover, we provide homologs of the stem‐cell markers vasa, piwi, and nanos, and investigate their expression patterns in gamete‐producing individuals for the first time in this group. We found no expression in females, while there is a distinct expression pattern in males. Based on this data, we argue that spermatogenesis starts in the gonads and finishes in the coelomic cavity, and it occurs simultaneously in a large number of segments. Surprisingly, no expression of the stem‐cell markers was found in the segment addition zone of these reproducing animals (stolonizing). Preliminary explanations like a lack of growth during stolonization, or the absence of a common genetic program between germ and somatic stem cells, are discussed. Finally, no reservoir of primordial cells has been detected, suggesting a possible epigenic origin of the Primordial Germ Cells of this species, though this hypothesis needs to be further investigated.